The global distribution of comorbid depression and anxiety in people with diabetes mellitus: Risk-adjusted estimates - Syed Shahzad Hasan; Alexandra M Clavarino; Abdullah Al Mamun; Suhail A. R. Doi; Therese Kairuz (Archives of Global Professionals, 2016)
Background: Previous reports suffer from the problem that they simply pooled data using aggregate means or standard meta-analytic method. The aim of the current study was to re-estimate the point prevalence of comorbid depression and anxiety in people with diabetes. Methods: The estimates were calculated using recently introduced directly standardized effect estimate method, which gives corrected risk-adjusted estimates for the population of interests. Reported are global and regional burden of prevalence, presented as risk-adjusted prevalence estimates with 95% confidence intervals. Results: Globally, the burden of comorbid depression was higher than the burden of anxiety (23.36% vs. 17.58%) symptoms and/or disorder in people with diabetes. There was a higher burden of comorbid depression in people living in developing regions (26.32%), in women (15.41%), and when assessed by self-report scales (SRS) (22.66%). The burden of anxiety was higher in developed regions in people with Type 2 diabetes mellitus (20.15%) and when assessed by SRS (20.75%). No statistically significant differences were observed due to gross heterogeneity across countries. Conclusions: There are wide-ranging differences in studies in developed and developing regions, regarding the burden of comorbid depression and of anxiety among people with diabetes and both conditions affect approximately a fifth of the diabetic population.